A BIBLIOMETRIC ANALYSIS OF EMPLOYEE DIGITAL LITERACY: CURRENT STATUS AND FUTURE RESEARCH DIRECTIONS - Zhang Ziqiong; Rosmah Mohammed; Rozanah Ab Rahman; Fang Fang , (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
This paper presents a bibliometric analysis of employee digital literacy, examining its status, scientific structure, and future research directions. Following the PRISMA diagram and employing bibliometric methods, the study evaluates academic articles on employee digital literacy, analyzing 99 selected articles through descriptive analysis, citation analysis, and cluster analysis. The results indicate a thriving development phase in the research on employee digital literacy. Noteworthy subject areas, influential authors, journals, articles, and countries have been identified. The present state of progress in this domain and five future directions are outlined through keywords and term co-occurrence analysis. Given the limited availability of literature reviews on employee digital literacy, this study contributes to the theoretical foundation and offers guidance for digital learning and training in academia. Organizations can strengthen their competitive edge by enhancing employee digital literacy and adapting effectively to digital transformation challenges.